Investigations on Average Fluorescence Lifetimes for Visualizing Multi-Exponential Decays - Li, Yahui; Natakorn, Sapermsap; Chen, Yu; Safar, Mohammed; Cunningham, Margaret; Tian, Jinshou; Li, David Day-Uei (Frontiers in Physics, 2020)
Intensity- and amplitude-weighted average lifetimes, denoted as τI and τA hereafter, are useful indicators for revealing Fo ̈rster resonance energy transfer (FRET) or fluorescence quenching behaviors. In this work, we discussed the differences between τI and τA and presented several model-free lifetime determination algorithms (LDA), including the centre-of-mass, phasor, and integral equation methods for fast τI and τA estimations. For model-based LDAs, we discussed the model-mismatch problems, and the results suggest that a bi-exponential model can well approximate a signal following a multi-exponential model. Depending on the application requirements, suggestions about the LDAs to be used are given. The instrument responses of the imaging systems were included in the analysis. We explained why only using the τI model for FRET analysis can be misleading; both τI and τA models should be considered. We also proposed using τA/τI as a new indicator on two-photon FLIM images, and the results show that τA/τI is an intuitive tool for visualizing multi-exponential decays.